ANALISIS RASIO KEUANGAN PERUSAHAAN YANG GO PUBLIK DI BURSA EFEK INDONESIA - Razak, A. (Journal of Accounting and Strategic Finance, 2010)
This research was aimed to test the financial ratio capability of Liquidity, Solvability, and Profitability in predicting the probability of appearing the financial distress condition in manufacturing companies that go public in Indonesia Stock Exchange. This research was based on the quantitative approach using the prediction technique of group membership, which tested statistically to hypothesis research using logistic regression backward stepwise method. The result showed that the financial ratio can be used to predicting financial distress condition in manufacturing companies that go public in Indonesia Stock Exchange. This was based on accuracy level shown in overall classification rate about 97.1%. But, this result was also indicating that not the entire financial ratio used, capable of predicting financial distress condition in companies. The ratio that dominated explaining the financial distress condition were Liquidity that proxy by QR and  Solvability that proxy by DTAR. Keywords: financial distress, financial ratio, logistic regression.